2008
DOI: 10.1007/s10040-008-0345-7
|View full text |Cite
|
Sign up to set email alerts
|

Relating groundwater to seasonal wetlands in southeastern Wisconsin, USA

Abstract: Historically, drier types of wetlands have been difficult to characterize and are not well researched. Nonetheless, they are considered to reflect the precipitation history with little, if any, regard for possible relation to groundwater. Two seasonal coastal wetland types (wet prairie, sedge meadow) were investigated during three growing seasons at three sites in the Lake Michigan Basin, Wisconsin, USA. The six seasonal wetlands were characterized using standard soil and vegetation techniques and groundwater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Hydrological research on kettle holes focused, either process-orientated (Pyzoha et al 2008;Johnson et al 2009;Voldseth et al 2009) or descriptive (Gamble and Mitsch 2009;Kahara et al 2009;Skalbeck et al 2009;Sumner et al 2009), on a limited number of study sites. Further, most ecological studies ignore the link between species occurrence and habitat dynamics of kettle holes (Luthardt and Dreger 1996;Schneeweiß 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Hydrological research on kettle holes focused, either process-orientated (Pyzoha et al 2008;Johnson et al 2009;Voldseth et al 2009) or descriptive (Gamble and Mitsch 2009;Kahara et al 2009;Skalbeck et al 2009;Sumner et al 2009), on a limited number of study sites. Further, most ecological studies ignore the link between species occurrence and habitat dynamics of kettle holes (Luthardt and Dreger 1996;Schneeweiß 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Downing (2010) has shown that these small bodies of water play an important role in the circulation of water and sediment not only in the regional but also global scale. Results of the studies of small water bodies on the American prairies (Woo & Rowsell, 1993;Winter & Rosenberry, 1995;Ferone & Devito, 2004;Skalbeck et al, 2009) have suggested that they are connected with groundwater reservoirs. This has also been demonstrated in a number of studies of moraine ponds in Mecklenburg, Germany (Lehsten, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The role of meteotsunami events in the hydrologic response, sediment budget, and system dynamics of incipient foredune/swale wetlands should be investigated further as these features often form the first line of defense for a resilient coastline. Subsurface water levels and retention can have substantial impact on the vegetation regime, nutrient cycling, and sediment stability of foredune‐swale type wetlands (e.g., Albert et al., 2005; Leira et al., 2019; Skalbeck et al., 2009; and others) and the influence of meteotsunami events on water availability, salinity (in the case of wetlands adjacent to seawater), and hydrogeomorphic evolution is a topic that merits further consideration.…”
Section: Discussionmentioning
confidence: 99%